2019
DOI: 10.3389/fgene.2019.01245
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differently Expressed Genes Associated With Prognosis and Growth in Colon Adenocarcinoma Based on Integrated Bioinformatics Analysis

Abstract: Latest statistics showed that the morbidity and mortality of colon adenocarcinoma (COAD) ranked fourth and fifth, respectively, around the world. COAD was a heterogeneous disease, and the high rates of recurrence, metastasis, and drug resistance still posed great challenges for treatment, which needs to further develop therapeutic and prognostic targets. In this study, we got the top 3,075 differentially expressed genes (DEGs) and 1,613 potential prognostic genes by GEPIA 2 and identified 1,166 fitness genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…[ 16 ] In a study on colon adenocarcinoma, it was also reported that high expression of the CCT6A promoted tumor cell growth, and was also associated with low survival rate of such patients. [ 12 ] CCT6A has also reported to be strongly association with survival and prognosis in renal cancer, with patients with altered CCT6A mRNA (stage I-IV) having significantly shorter OS compared to healthy controls. [ 4 ] Thus, the CCT6A gene plays a key role in the development and prognosis prediction of many tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] In a study on colon adenocarcinoma, it was also reported that high expression of the CCT6A promoted tumor cell growth, and was also associated with low survival rate of such patients. [ 12 ] CCT6A has also reported to be strongly association with survival and prognosis in renal cancer, with patients with altered CCT6A mRNA (stage I-IV) having significantly shorter OS compared to healthy controls. [ 4 ] Thus, the CCT6A gene plays a key role in the development and prognosis prediction of many tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological processes regulated by these genes were closely related to tumors. The high expression of DDOST in colon adenocarcinoma promotes the proliferation of tumor cells [20]. The expression of RCC2 in ER-positive breast induces the expression of IGF-1 and leads to the malignant behavior of tumor cells, including proliferation, invasion, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Klimczak M used the TCGA database to identify the overexpression of CCT6A in breast cancer as a signi cant contributor to poor prognosis [21] . In a study on colon adenocarcinoma, it was pointed out that high expression of the CCT6A promoted the growth of colon adenocarcinoma cells on the one hand, and was associated with low survival rate of colon adenocarcinoma on the other [22] . CCT6A also showed a strong association with survival and prognosis in renal cancer, with patients with altered CCT6A mRNA (stage I-IV) having signi cantly shorter overall survival compared to healthy controls [23] .…”
Section: Discussionmentioning
confidence: 99%